Leading Indicators of Fiscal Distress : Evidence from the Extreme Bound Analysis - Bruns, Martin (IMF Working Papers; Working Paper, 2016)
Early warning systems (EWS) are widely used for assessing countries' vulnerability to fiscal distress. Most EWS employ a specific set of only fiscal leading indicators predetermined by the researchers, which casts doubt on their robustness. We revisit this issue by using the Extreme Bound Analysis, which allows identifying robust leading indicators of fiscal distress from a large set. Consistent with the theoretical predictions of latest generation crisis models, we find that both fiscal (e.g., fiscal balance, foreign exchange debt) and non-fiscal leading indicators (e.g., output, FX reserves, current account balance, and openness) are robust. In addition, we find that a fiscal vulnerability indicator based on fiscal and non-fiscal leading indicators offers a 29% gain in predictive power compared to a traditional one based on fiscal leading indicators only. It also has good predictive power out of sample, with 78 percent of crises predicted correctly and only 34 percent false alarms issued for the period 2008-15. This suggests that both fiscal and non-fiscal leading indicators should be taken into account when assessing country's vulnerability to fiscal distress.